Nivel de conocimientos y vías de transmisión sexual de la Hepatitis B en los estudiantes de 3er año de bachillerato de la Unidad Educativa Marista del cantón Paltas. - Jumbo Tandazo, Gabriela del Cisne (2013)
This research work is qualitative transverse, which developed in the context of determining the degree of knowledge of hepatitis B, its risk factors and sexual routes of transmission, conducted 82 students, 46 men and 36 women of the 3rd year of high school Marist Educational Unit – Paltas; information obtained through a survey, previously informed consent. Based on the results, it is established that the level of knowledge of hepatitis B, HALF, at 58.7% male and 52.8% female, while the level of knowledge of risk factors is GOOD category, both male and female with 69.6% to 63.9%, regardless of age meeting the highest percentage in those between 16 and 17 years. However the level of knowledge of sexual routes of transmission is better in the students; VERY GOOD category, with 36.1%, while students, GOOD category, with 43.5% and in terms of age, the highest percentage is at 17 years, with VERY GOOD and GOOD, both with 23.2%. As part of the foregoing applies an intervention program, to developing and delivering lectures and triptychs to students and teachers KEYWORDS: knowledge of hepatitis B, sexual routes of transmission, risk factors, Marist Educational Unit.